The Useful Myth - Stanford Wyatt (Oz, 1988)
The Useful Myth is a story that in some oblique but suggestive way tells about the design intentions related to a work of architecture. This narrative permits intellectual and emotional access to the architectural ideas of a building and in so doing becomes an essential part of the building's existence...